Pengaruh Pupuk Anorganik Terhadap Pertumbuhan dan Hasil Kacang Hijau (Vigna Radiata L.) Varietas Vima 1 dan Demak - Arintoko, Arif Nurcahyo; Maryani, Yekti; Pamungkas, Djoko Heru (JURNAL ILMIAH AGROUST, 2023)
The purpose of this study was to determine the effect of mixed inorganic fertilizer treatments and varieties on the growth and yield of green beans (Vigna radiata L.) varieties Vima 1 and Demak. The research was conducted in September December 2022, in Bungkus Hamlet, Parangtritis Village, Kretek District, Bantul Regency, I.Y. with an altitude of ± 10 m above sea level with an average annual rainfall of 1400 – 1900 mm/year, soil pH 5.6 – 6.0, air humidity 65 – 85%, light intensity 12 hours, light length between 400 – 550 mm and average temperature 24 32 ºC. This research was carried out with 2 repetitions using a Completely Randomized Block Design (RAKL) covering two factors, namely the type of inorganic fertilizer consisting of (NPK, NP, NK, and PK) and the variety consisting of (Vima 1 and Demak). Analysis of the results was carried out on the results of observations using variance at the 5% level of significance, the difference between the treatments was tested with the DMRT (Duncan's Multiple Range Test) at the 5% level. The results of the analysis showed that the types of inorganic fertilizers and varieties showed no interaction on all growth and yield variables of mung bean plants, the types of inorganic fertilizer treatments showed no significant difference on the growth of mung bean plants, the treatment of varieties showed no significant differences in the growth of mung bean plants. , the mixed NPK fertilizer treatment gave the highest green bean yields, the Vima 1 variety treatment gave higher mung bean yields compared to the Demak variety.